FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN SERTA DAMPAKNYA TERHADAP MINAT BELI ULANG KONSUMEN (STUDI PADA BLENDS PASTA & CHOCOLATE CABANG UNIKA SEMARANG) - Putri, Anindya Dwiana; Tri Astuti, Sri Rahayu (Diponegoro Journal of Management, 2017)
Culinary businesses are keep  booming and growing nowadays, which causing a tighter  competition between all culinary businesses’ owners. The main purpose of this research is  to get to know if there’s any impact of product quality, service quality  and customer value on customer repurchase intention at Blends Pasta & Chocolate Unika Semarang with customer satisfaction as the intervening variable.A total  sample of 100 respondents are taken by purposive sampling technique and all obtained from Blends Pasta & Chocolate’s Unika Semarang customers who purchased at least 2 times before. All data are collected from both  opened and closed questions on questioner’s answer. The method for analyzing data is using  double regression method on SPSS 21 version.The result from data analysis  showed that product quality, service quality, and customer value variables have all positive and significant impact toward customer satisfaction  with  coefficient regression Y1=0,354X1 + 0,276X2 + 0,275X3. Meanwhile costumer satisfaction’s variable has positive and significant impacts toward customer repurchase intention variable with coefficient regression Y2 = 0,747Y1.